TGFÎ²1-mediated expression and alternative splicing of Fibronectin Extra Domain A in human podocyte culture - Madne, Tarunkumar Hemraj; Dockrell, Mark Edward Carl (Cellular and Molecular Biology, 2018)
Alternative splicing is a fundamental phenomenon to build protein diversity in health and diseases. Extra Domain A+ Fibronectin (EDA+Fn) is an alternatively spliced form of fibronectin protein present in the extra cellular matrix (ECM) in renal fibrosis. Podocytes are spectacular cell type and play a key role in filtration and synthesise ECM proteins in renal physiology and pathology. TGFÎ²1 is a strong stimulator of ECM proteins in renal injury. In this study, we have investigated alternative splicing of EDA+ Fn in human podocytes in response to TGFÎ²1. We have performed western blotting and immunofluorescence to characterise the expression of the EDA+Fn protein, real-time PCR for RNA expression and RT-PCR to look for alternative splicing of EDA+Fn in conditionally immortalised human podocytes culture.We used TGFÎ²1 as a stimulator and SB431542 and SRPIN340 for inhibitory studies. In this work, for the first time we have demonstrated in human podocytes culture EDA+Fn is expressed in the basal condition and TGFÎ²1 2.5ng/ml induced the Fn mRNA and EDA+Fn protein expression demonstrated by real-time PCR, western blotting and immunofluorescence. TGFÎ²1 2.5ng/ml induced the alternative splicing of EDA+Fn shown by conventional RT-PCR. Studies with ALK5 inhibitor SB431542 and SRPIN340 show that TGFÎ²1 induced alternative splicing of EDA+Fn was by the ALK5 receptor and the SR proteins. In human podocytes culture, alternative splicing of EDA+Fn occurs at basal conditions and TGFÎ²1 further induced the alternative splicing of EDA+Fn via ALK5 receptor activation and SR proteins. This is the first evidence of basal and TGFÎ²1 mediated alternative splicing of EDA+Fn in human podocytes culture.